PKM Peningkatan Kompetensi Guru SMK Dalam Bidang Komputer Akuntansi - Nayang Helmayunita; Vanica Serly; Helga Nuri Honesty (Universitas Negeri Padang, 2019)
The MYOB and Spreadsheet program is an accounting program taught at the Vocational Business and Management. Both of these programs are test material on the Expertise Competency Test. But with the development of technology, there are several other programs that need to be mastered by the students, which is accurate accounting program. Accurate programs have been widely used by companies in managing finances. For the reason, the Vocational School of Business and Management should answer the challenges of the times by introducing this program as additional expertise for their students. From this problem, the Computer Accounting training program for Vocational School Business and Management teachers is needed as an effort to improve teacher understanding and competence. The training programs are: Spreadsheets, and Accurate. This training is given to teachers of Vocational Business and Management in the Kabupaten Pesisir Selatan. This area was chosen because, vocational teachers in the South of West Sumatra have difficulty accessing competency and science development training. Implementation of these activities take place from 4-7 September 2019. The implementation is done in three stages, namely the stages of exposure of the material, the integrated exercise phases and stages of evaluation. At the end of the activity it was found that there was an increase in the understanding of the participants regarding the concept of computer accounting with a value level of understanding that could be achieved was 80%. As for understanding the practice of preparing financial statements using an accounting program, participants can complete cases with a completion rate of 86.20% for the accurate program, and 93.10% for the spreadsheet. Furthermore, the improvement in teacher competency is expected to be transferred to students and reflected in the value of the Skills Competency Examination and the acceptance of graduates in the world of work.Keywords: Competence, accourate, spreadsheet, excel